Development of Augmented Reality Technology Applications Gadget Based - Nursamsu Nursamsu; Allif Syahputra Bania; Tri Mustika Sarjani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The development of augmented reality technology applications using gadget media can be used as a source of learning that occurs in cyberspace to become real. As for the purpose of the study is to determine the feasibility test and student response to the development of gadget-based augmented reality technology applications. The method in this research is a development approach or Research and Development (R&D). The subject of product validation was carried out by several experts, namely media experts, material experts and practitioners (science teachers). Furthermore, the subject of product testing was carried out by students of SMA Muhammadiyah Kota Langsa consisting of 20 science class students.